Pengaruh Latihan Knee Tuck Jump dan Barier Hops terhadap Kualitas Tendangan Bola Lambug Jauh - Katno, Katno; , Wahyuni, S.Fis.,Ftr.,M.Kes; , Agus Widodo, S.Fis.,Ftr., M.Fis (2015)
Background: The Decline of sports achievement is determined by lack of exercise and physical needs analysis in sports, particularly football games. Physical exercise, techniques, leg strength are very important in football practice, since the main movement in this game is kicking. To kick well, such as long distance kick needs good legs strength. The Exercise of knee tucks jumps and hops barrier is one of the leg muscle strengthening exercises which are needed in foot ball practice. Objective: The objective of this research were to determine the effects of knee tuck jumps and hops barrier exercise toward the quality of long distance ball kicks at SSB Singoprono, Simo, Boyolali and to find out the differences effect of knee tuck jump and barrier hops exercise toward the quality of long distance ball kick at SSB Simo, Boyolali. Research Methods: This research applied experimental design by using Quasi Experimental approach where all variable were controlled by the researcher. Result: Based on the data analysis test done by using paired sample t-test showed that there were significant effect of knee tuck jump and barrier hops exercise toward the quality of long distance ball kick with p value p(0,000)<0,05 P(0,044)<0,05. Meanwhile data analysis done by using independent sample t-test showed the value of p(0,001)<0,05 means that Ha is accepted, there were significant effects of knee tuck jump and barrier hops exercise toward the quality of long distance ball kick. Conclusion: There were differences of effect between knee tuck jump exercise and barrier hops exercise. Key words: knee tuck jump, barrier hops, long distance ball kick quality